(untitled) (Biological Sciences - PJSIR, 1999)
Using pure culture experiments, the effect of alachlor and haloxyfop at IOOl-lgactive ingredient rnl’ on wheat straw degradation by six fungal species were investigated. The followingparameters wereexamined: the weight loss, CO2 evolution, C-and N-mineralization. The used rates of both herbicides inhibited wheat straw breakdown by five (out of six) fungal species. However, the decay of wheat straw inoculated with Aspergillus niger was accelerated by haloxyfop (at the two concentrations used) and alachlor (at 100 I-lgml’ only).